Unraveling the Mechanism of Different Kinetics Performance between Ether and Carbonate Ester Electrolytes in Hard Carbon Electrode - Yi, Xiaoli; Li, Xinhai; Zhong, Jing; Wang, Siwu; Wang, Zhixing; Guo, Huajun; Wang, Jiexi; Yan, Guochun (Advanced functional materials, 2022)
Ether electrolytes exhibit better rate kinetics than carbonate ester electrolytes when used in several kinds of anode materials, especially in hard carbon (HC) for sodium‐ion batteries (SIBs). However, the mechanism causing the remarkable kinetics difference is still unclear. Here, a three‐electrode system is used first to eliminate the influence of polarization from the Na counter electrode. Then, there is systematic exploration from three steps of the electrode reaction process (Na+ storage in HC; de‐solvation; Na+ migration through solid electrolyte interphase (SE), and the underlying mysteries are uncovered. For Na+ storage in the bulk of the HC, it is found that two systems show the same storage mechanism and Na metallic nanoparticles will appear when discharged to 0.1 V. In addition, faster de‐solvation of the ether electrolyte is uncovered by three‐electrode temperature‐dependent EIS and solvation free energies calculation. Moreover, the difference of the SEI layers is unraveled by X‐ray photoelectron spectroscopy etching, scanning electron microscopy, and differential electrochemical mass spectrometry. Most importantly, by discriminating the impacts of the SEI layers and de‐solvation behavior, it can be concluded that the de‐solvation process is the rate‐controlling step of the electrode reaction process and is the main factor causing the kinetics differences between the two electrolytes. The research provides a clear mechanism to illuminate fast kinetics for ether electrolytes, which will promote its application in SIBs. Hard carbon electrodes show the same Na+ ion storage mechanism in two electrolytes. Ether electrolytes are favorable for a faster de‐solvation process. Solid electrolyte interphase (SEI) layers with more inorganic component and uniform morphology also favor faster Na+ ion transport for ether electrolytes. The de‐solvation behavior has a more profound effect than the SEI layers and is the main factor inducing the difference in kinetics.